2010
DOI: 10.1016/j.ajog.2010.02.019
|View full text |Cite
|
Sign up to set email alerts
|

17-alpha-hydroxyprogesterone caproate for the prevention of preterm birth in women with prior preterm birth and a short cervical length

Abstract: Objective To evaluate 17-alpha hydroxyprogesterone caproate (17P) for prevention of preterm birth (PTB) in women with prior spontaneous PTB (SPTB) and cervical length (CL) <25mm. Study Design Planned secondary analysis of the NICHD-sponsored randomized trial evaluating cerclage for women with singleton gestations, prior SPTB (17-33 6/7weeks), and CL<25mm between 16-22 6/7weeks. Women were stratified at randomization to intent to use or not use 17P. The effect of 17P was analyzed separately for cerclage and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
2
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(67 citation statements)
references
References 25 publications
4
55
2
6
Order By: Relevance
“…Rafael et al , in a retrospective cohort study of 58 women with CL of < 25 mm at < 23 6/7 weeks' gestation, found that there was no significant differences in the incidences of spontaneous PTB < 35, < 32, or < 28 weeks' among women with a ultrasound indicated cerclage, regardless of whether or not they received 17OHP-C (15 in the 17OHP-C group vs. 43 in the no 17OHP-C group) during the current pregnancy. Their findings are similar to the results of two other studies concerning 17OHP-C in women with a cerclage in place (Berghella et al, 2010 andRebarber et al, 2008).…”
Section: Progestins and Short Cervixsupporting
confidence: 91%
“…Rafael et al , in a retrospective cohort study of 58 women with CL of < 25 mm at < 23 6/7 weeks' gestation, found that there was no significant differences in the incidences of spontaneous PTB < 35, < 32, or < 28 weeks' among women with a ultrasound indicated cerclage, regardless of whether or not they received 17OHP-C (15 in the 17OHP-C group vs. 43 in the no 17OHP-C group) during the current pregnancy. Their findings are similar to the results of two other studies concerning 17OHP-C in women with a cerclage in place (Berghella et al, 2010 andRebarber et al, 2008).…”
Section: Progestins and Short Cervixsupporting
confidence: 91%
“…In singleton gestations with prior SPTB and a short TVU CL <25mm before 23 weeks, 17P was associated with statistically significant decrease in PTB <24 weeks and perinatal death in women not receiving cerclage in a secondary analysis of a cerclage trial (45). Beneficial effects of 17P were noted primarily for women with CL15-24.9 mm, while they were nonsignificant for women with CL <15 mm.…”
Section: Pmentioning
confidence: 86%
“…A control group of usual care or placebo was compared with progesterone (either type) in 17 studies, [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] with cerclage in 12 studies [44][45][46][47][48][49][50][51][52][53][54][55] and with pessary in three studies. [56][57][58] In addition, one study compared 17-OHPC with cerclage 59 and three studies compared natural progesterone with 17-OHPC [60][61][62] (Table 1, and see Supporting information, Figure S2).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…57 In the one study including only women with both previous PTB and short cervix (≤25 mm), cerclage significantly reduced PTB < 37 weeks (OR 0.52; 95% CI 0.29-0.90). 54 When progesterone was studied according to type of progesterone (either natural progesterone [per vagina or oral] or 17-OHPC), only natural progesterone significantly reduced PTB < 34 weeks (OR 0.38; 95% CrI 0.19-0.69; NNT 8; low quality; Table 3). Both natural progesterone and 17-OHPC significantly reduced PTB < 37 weeks (natural progesterone, OR 0.54; 95% CrI 0.36-0.76; NNT 8; moderate quality; 17-OHPC, OR 0.65; 95% CrI 0.42-0.96; NNT 11; moderate quality).…”
Section: Subgroup Analysesmentioning
confidence: 99%